Racisms : from the Crusades to the Twentieth Century - Bethencourt, Francisco (Princeton University Press, 2013)
"Groundbeaking in its global and historical scope, Racisms is the first comprehensive history of racism, from the Crusades to the twentieth century. Demonstrating that there is not one continuous tradition of racism in the West, distinguished historian Francisco Bethencourt shows that racism preceded any theories of race and must be viewed within the prism and context of social hierarchies and local conditions. In this richly illustrated book, Bethencourt argues that in its various aspects, all racism has been triggered by political projects monopolizing specific economic and social resources. Bethencourt focuses on the Western world, but opens comparative views on ethnic discrimination and segregation in Asia and Africa. He looks at different forms of racism, particularly against New Christians and Moriscos in Iberia, black slaves and freedmen in colonial and postcolonial environments, Native Americans, Armenians in the Ottoman Empire, and Jews in modern Europe. Exploring instances of enslavement, forced migration, and ethnic cleansing, Bethencourt reflects on genocide and the persecution of ethnicities in twentieth-century Europe and Anatolia. These cases are compared to the genocide of the Herero and Tutsi in Africa, and ethnic discrimination in Japan, China, and India. Bethencourt analyzes how practices of discrimination and segregation from the sixteenth to the nineteenth centuries were defended, and he systematically integrates visual culture into his investigation."--Publisher's description